2006
DOI: 10.2325/jbcs.13.225
|View full text |Cite
|
Sign up to set email alerts
|

A case of breast cancer metastatic to the tail of the pancreas

Abstract: Breast cancer metastasis to pancreas is rarely seen. There have been only 6 cases described in the literature. We present the seventh case of a 54-year-old woman with breast cancer that metastasized to the tail of the pancreas 4 years and 4 months after radical mastectomy. Although the serum levels of CA15-3 and TPA had gradually increased without symptoms, it was difficult to establish the diagnosis before contrast-enhanced abdominal CT scan was performed. Immunohistochemical staining using E-cadherin was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Positive CA15-3 tissue staining is thought to be specific to breast cancer. [6] In a review of 264 breast cancer patients, the uvea was the first systemic metastatic site of previously diagnosed breast cancer in 43 (16%) patients. [7] Freedman et al [8] reviewed the charts of 112 patients (141 eyes) presenting with a metastasis to the eye or orbit and revealed that the average time from the breast cancer diagnosis to metastasis to the eye and orbit was approximately 4 years (1266 days).…”
Section: Discussionmentioning
confidence: 99%
“…Positive CA15-3 tissue staining is thought to be specific to breast cancer. [6] In a review of 264 breast cancer patients, the uvea was the first systemic metastatic site of previously diagnosed breast cancer in 43 (16%) patients. [7] Freedman et al [8] reviewed the charts of 112 patients (141 eyes) presenting with a metastasis to the eye or orbit and revealed that the average time from the breast cancer diagnosis to metastasis to the eye and orbit was approximately 4 years (1266 days).…”
Section: Discussionmentioning
confidence: 99%
“…Resection should be considered for metastases to the pancreas in the absence of generalised metastatic disease, but surgery may contribute to prolonged survival and offers significant palliation even in extended extrapancreatic disease [8,9]. Endoscopic palliation or chemotherapy alone could be considered too.…”
Section: Discussionmentioning
confidence: 99%
“…Lobular carcinoma was demonstrated in 8 cases, signetring cells in one, comedo type in another and scirrhous type in another of the 11 treated cases. The disease free interval varies from 16 to 84 months (mean 43.3), and the interval of our case was 24 months without any symptoms [2,[4][5][6][7][8][9][10][11].…”
Section: Conflict Of Interestmentioning
confidence: 94%
“…In the literature, we found 11 cases of solitary metastases to the pancreas [2,[4][5][6][7][8][9][10][11] and the dissemination to the pancreatic head is more common than to the pancreatic tail. Lobular carcinoma was demonstrated in 8 cases, signetring cells in one, comedo type in another and scirrhous type in another of the 11 treated cases.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation